An efficient S-band erbium-doped fiber amplifier using double-pass configuration - Harun, Sulaiman Wadi; Saat, Nor Kamilah; Ahmad, Harith (2005)
An efficient short wavelength band erbium-doped fiber amplifier (S-band EDFA) is proposed and demonstrated using double-pass configuration. This amplifier provides a gain as high as 30 dB, but using only 15 m depressed cladding erbium-doped fiber (EDF) and 130 mW of 980 nm pump power. Compared to the single-pass configuration, this amplifier shows a gain enhancement of about 14 dB for pump powers above 120 mW. However, noise figures penalties of about 0.5 similar to 0.9 dB are obtained for these pump powers. The proposed double-pass amplifier will play an important role in the development of a practical S-band EDFA from perspective of economical usage of EDF and pump power.